Allergic Reactions With Intravenous Compared With Intramuscular Pegaspargase in Children With High-risk Acute Lymphoblastic Leukemia: A Population-based Study From the Maritimes, Canada. Issue 5 (July 2016) - MacDonald, Tamara; Kulkarni, Ketan; Bernstein, Mark; Fernandez, Conrad V.
Abstract : Intravenous (IV) administration of pegaspargase in children with acute lymphoblastic leukemia (ALL) may be associated with an increased risk of allergic reactions, and thus the need for more costly intramuscular (IM) erwinia asparaginase. In 128 patients allergic reactions were documented in 3% and 14% of those who received IM and IV pegaspargase, respectively ( P =0.029). These reactions were primarily contributed to by high risk (HR)-ALL patients ( P< 0.01). The possible decreased efficacy and quality of life and the substantial costs entailed by switching from IV pegaspargase to IM erwinia should prompt reconsideration of the IV administration route for pegaspargase in HR-ALL patients.